2018
DOI: 10.1002/adfm.201802001
|View full text |Cite
|
Sign up to set email alerts
|

Smart Anisotropic Wetting Surfaces with Reversed pH‐Responsive Wetting Directions

Abstract: Smart pH‐responsive surfaces that could autonomously induce unidirectional wetting of acid and base with reversed directions are fabricated. The smart surfaces, consisting of chemistry‐asymmetric “Janus” silicon cylinder arrays (Si‐CAs), are prepared by precise modification of functional groups on each cylinder unit. Herein, amino and carboxyl groups are chosen as typical pH‐responsive groups, owing to their protonation/deprotonation effect in response to pH of the contacted aqueous solution. One side of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…[ 18–21 ] Recent advances have brought diverse approaches to create specific wetting performance by using chemical treatment, [ 22–24 ] dedicated pattern designs, [ 25–27 ] and functional materials. [ 28,29 ] Notably, Quéré and co‐workers [ 16 ] manipulated the droplet shape on an elastic surface with soft pillars. Park and Kim used a shape memory polymer‐based structure to shape droplets with adjustable surface morphology.…”
Section: Figurementioning
confidence: 99%
“…[ 18–21 ] Recent advances have brought diverse approaches to create specific wetting performance by using chemical treatment, [ 22–24 ] dedicated pattern designs, [ 25–27 ] and functional materials. [ 28,29 ] Notably, Quéré and co‐workers [ 16 ] manipulated the droplet shape on an elastic surface with soft pillars. Park and Kim used a shape memory polymer‐based structure to shape droplets with adjustable surface morphology.…”
Section: Figurementioning
confidence: 99%
“…Patterning has proved to be useful to introduce a new dimension of functionality at interfaces. For example, Ge et al reported pH‐responsive surfaces that could differentiate between basic and acidic aqueous solutions and show an inverse anisotropic wetting behavior ( Figure a–f) . Key elements are Janus silicon cylinder arrays (Si‐CAs).…”
Section: Response Through Patterningmentioning
confidence: 99%
“…f) Photographs of droplets at pH values between 0.98 and 13.05. Adapted with permission . Copyright 2018, Wiley‐VCH.…”
Section: Response Through Patterningmentioning
confidence: 99%
“…[20] Furthermore, 2-(Dimethylamino) ethyl methacrylate (DMAEMA), which is a kind of intelligent polymer with both temperature and pH sensitivity, has been a potential polycationic carrier and can adjust the phase transition at 14 ∼ 50°C with the protonation degree of the side chain tertiary amine group, both in vitro and in vivo. [21] Combining PEI and PDMAEMA could improve transgene expression efficiency without decreasing cell viability for in vivo systems, and make it a potential combination of applications in biomaterials. [22,23] These reports suggested that, for stimuliresponsive system, the effective combination of cellulose, PEI and PDMAEMA would benefit from an integrative strategy, but is this technically possible?…”
Section: Introductionmentioning
confidence: 99%